Secrets & spies Inferno - Macauley, Jo (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2015)
In 1666 Beth Johnson, celebrated actress and spy, and her friends, John and Ralph work to rescue John's sister from the assassin who is trying to kill King Charles--but a great fire is about to consume London
A gift from book Africa
1 2 13
Keywords: Actors -- Great Britain -- Juvenile fiction; Assassins -- Juvenile fiction